Forensic Anthropological Significance of Dental Calculus Deposits as Proxy Identifier of the Host and the Oral Microbiota: A Scoping Review - Sehrawat, Jagmahender Singh; Thakur, Shubham (Anthropological Review, 2025)
Dental calculus is a creamish-yellow to brownish-black hard crust deposited on teeth, having the dietary micro-remains, biomolecules, oral microbes and the secretions preserved in it over a long period of time. It has served as a valuable source material for research in diverse scientific disciplines such as anthropology, archaeology, microbiology and forensic sciences. The host and microbial DNA extracted and sequenced from dental calculus deposits (DCD) have helped to establish the identity of unknown individuals, and also the use of certain drugs, tobacco products by the individuals of the past as well as contemporary human populations. The entrapped cellular as well as tissue fragments in calculus can help in identification, reconstruction of dietary habits, food practices, manner of death/pathologies the geographical and occupational affinity of ancient human remains. Calculus deposits gleaned from the archaeological or paleontological specimens can be used to assess the shifts in oral microbiota compositions and host-pathogen co-evolution as researchers have found calculus as rich source of oral microbiomes, pathogens, dietary biomolecules, and host DNA. Advancing dental calculus research through validation studies, technological innovations, interdisciplinary collaborations, longitudinal research, and ethical considerations holds promise for its robust forensic anthropological utilizations. The current status of anthropological, archaeological and microbial research involving dental calculus deposits, future challenges, and its forensic anthropological significance are presented in this review article.